Analysis of Behavioral Intentions of Health Protocol Discipline During The COVID-19 Pandemic Using Theory of Planned Behavior (TPB) and Health Belief Model (HBM) - Moh Erfan Arif; Rila Anggraeni; Nadiyah Hirfiyana Rosita (APMBA (Asia Pacific Management and Business Application), 2022)
This study aims to determine the effect of subjective norm, attitude toward behavior, perceived behavioral control, perceived susceptibility, perceived severity, and perceived benefit on the intention to discipline health protocols in Indonesia during the COVID-19 pandemic. The combination of variables analyse in this study has never been studied before. The population of this study is the Indonesian sampled 241 respondents with non-probability sampling technique and using a purposive sampling method. Data were collected using a questionnaire with a five-level Likert scale. This research uses multiple linear regression analysis methods with SPSS software. The results showed that the variables attitude toward behavior, subjective norm, perceived behavioral control, perceived susceptibility, perceived severity, and perceived benefit had a significant effect on the disciplinary intention of health protocols in Indonesia during the COVID-19 pandemic.